FOCUS GROUP DISCUSSION (FGD) UNTUK MENINGKATKAN MINAT BELAJAR PENDIDIKAN AGAMA ISLAM - Ramadhani, Yunita Fitri; Inayati, Nurul Latifatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This research aims to determine the learning carried out at SMA Batik 2 Surakarta, especially in the learning process in Islamic Religious Education, when in the learning process students are only listeners during the learning process and do not actively participate in teaching activities. This can cause students to become less motivated to learn. So, it is necessary to develop an appropriate strategy to significantly improve Islamic Religious Education learning at SMA Batik 2 Surakarta. Focus Group Discussion (FGD) is another method of motivating student learning, especially in Islamic Religious Education subjects. Focus Group Discussion is a form of discussion that can help students gain a deeper understanding of the learning topics they are studying, thereby attracting students' attention and motivating them in the learning process. After using the group discussion method (FGD), students will be more enthusiastic and active in the learning process because in this case, each student can exchange ideas. The research method used is descriptive qualitative. This research was conducted at SMA Batik 2 Surakarta using interview methods and direct observation with Islamic Religious Education teachers who taught at SMA Batik 2 Surakarta. Then the subject used by the researcher was XI IPS 1.